GE_GERICHTE C/1366/2007 vom 28. Mai 2009 - GE Cour de justice (2009)
; PARTAGE(SENS GÉNÉRAL) ; PRÉVOYANCE PROFESSIONNELLE ; INDEMNITÉ(EN GÉNÉRAL) ; OBLIGATION D'ENTRETIEN ; PERSONNE DIVORCÉE | CC.124.1. CC.125